Impact of Mitragyna speciosa methanolic extract on adaptive immunity: investigated in SRBC-induced delayed-type hypersensitivity mouse model - Hassan, Masriana; Ramasamy, Rajesh; Mahayidin, Hasni; Elsalamı, Rabıa Mrehıl; Abd Rahman, Shamima; Kalifa Kafo, Anwar Salm (Universiti Putra Malaysia, 2024)
Introduction: Mitragyna speciosa (Korth.) or Kratom contains several bioactive compounds that have potential therapeutic benefits. The present study investigated the potential immunomodulatory effects of Mitragyna speciosa methanolic extract (MSME) in delayed-type hypersensitivity (DTH) mouse model. Materials and methods: Female Balb/c mice were induced with DTH by sheep red blood cells (SRBCs) following the administration of MSME. The thickness of paw edema that developed following subcutaneous injection of SRBC on the right hind footpad of the mice was measured. The blood samples and spleen were collected for investigation of the effects of MSME on antibody production, complete blood count (CBC), spleen index, splenocyte proliferation, and lymphocyte (CD4, CD8, and CD19) populations. Results: The data demonstrated that MSME significantly reduced the paw edema induced by SRBC and showed a marked reduction in anti-SRBC antibody levels. However, no significant changes were observed in the CBC, spleen index, and CD4, CD8, and CD19 subset populations. In addition, stimulation of splenocytes isolated from MSME-treated SRBC-induced DTH mice with lipopolysaccharide (LPS) or Concanavalin A (Con A) ex vivo reduced cell proliferation. Conclusion: These data demonstrated that MSME potentially inhibits immune response by suppressing DTH reactions, reducing antibody production and cell proliferation without affecting the lymphocyte profiles. These findings suggest the immunomodulatory effects of MSME through immunosuppressive and anti-inflammatory activities.